Insulin-like growth factor family and prostate cancer: new insights and emerging opportunities - Elemam, Noha M.; Hotait, Hassan Youssef; Saleh, Mohamed A.; El-Huneidi, Waseem; Talaat, Iman M. (Frontiers in Endocrinology, 2024)
Prostate cancer is the second most commonly diagnosed cancer in men. The mammalian insulin-like growth factor (IGF) family is made up of three ligands (IGF-I, IGF-II, and insulin), three receptors (IGF-I receptor (IGF-1R), insulin receptor (IR), and IGF-II receptor (IGF-2R)), and six IGF-binding proteins (IGFBPs). IGF-I and IGF-II were identified as potent mitogens and were previously associated with an increased risk of cancer development including prostate cancer. Several reports showed controversy about the expression of the IGF family and their connection to prostate cancer risk due to the high degree of heterogeneity among prostate tumors, sampling bias, and evaluation techniques. Despite that, it is clear that several IGF family members play a role in prostate cancer development, metastasis, and androgen-independent progression. In this review, we aim to expand our understanding of prostate tumorigenesis and regulation through the IGF system. Further understanding of the role of IGF signaling in PCa shows promise and needs to be considered in the context of a comprehensive treatment strategy.